Topical therapies for the treatment of plaque psoriasis: systematic review and network meta‐analyses. (25th April 2013) - Samarasekera, E.J.; Sawyer, L.; Wonderling, D.; Tucker, R.; Smith, C.H.
Summary The majority of people with psoriasis have localized disease, where topical therapy forms the cornerstone of treatment. We set out to summarize evidence on the relative efficacy, safety and tolerability of different topical treatments used in plaque psoriasis. We undertook a systematic review and meta‐analyses of randomized trial data of U.K.‐licensed topical therapies. The primary outcome was clear or nearly clear status stratified for (i) trunk and limbs; and (ii) scalp. Network meta‐analyses allowed ranking of treatment efficacy. In total, 48 studies were available for trunk and limb psoriasis, and 17 for scalp psoriasis (22 028 patients in total); the majority included people with at least moderate severity psoriasis. Strategies containing potent corticosteroids (alone or in combination with a vitamin D analogue) or very potent corticosteroids dominated the treatment hierarchy at both sites (trunk and limbs, scalp); coal tar and retinoids were no better than placebo. No significant differences in achievement of clear or nearly clear status were observed between twice‐ and once‐daily application of the same intervention or between any of the following: combined vitamin D analogue and potent corticosteroid (applied separately or in a single product), very potent corticosteroids, or potent corticosteroids (applied twice daily). Investigator and patient assessment of response differed significantly for some interventions (response rates to very potent corticosteroids: 78% and 39%, respectively). No significant differences were noted for tolerability or steroid atrophy, but data were limited. In conclusion, corticosteroids are highly effective in psoriasis when used continuously for up to 8 weeks and intermittently for up to 52 weeks. Coal tar and retinoids are of limited benefit. There is a lack of long‐term efficacy and safety data available on topical interventions used for psoriasis.